Process Parameter Optimization Of Adhesive Dispense Machine - Teo, Boon Guan (2018)
Adhesive dispense applications that discussed in this study relate to the process parameter optimization of adhesive dispense machine for Surface Mount Technology (SMT) Applications. SMT Adhesive dispensing process is the process of transferring adhesive onto the PCB solder mask in a position suitable for holding the later placed components until the PCB is wave soldered. It is also used to hold heavy components in the second pass of a double-sided reflow process. This document provides practical guidelines for the dispensing of adhesive materials for those manufacturing using surface mount technology. There are two common failures relate to SMT adhesive dispensing, they are missing components and open joints. Dispensing is a complex process with many different controllable parameters. It is difficult to setup machine parameters. Dot dispensing sensitive to the level of the adhesive viscosity and its impacts to machine setup. A different batch of the same material may differ in viscosity. The rheological properties of materials often change with time and this causing difficult to sustaining the dispensing process. This study guide on how to set up the machine, identify machine parameters, understand the dispense application, analyze the stability of dispense machine by X Y axis repeatability, dot diameter repeatability, and dot weight repeatability. Nevertheless, optimizing machine dispense parameters by using Taguchi method design of experiment approach to get the best dispense parameters to range with the filter the adhesive viscosity noise and continue sustain of the dispensing process. From the stability test dispense results, Camalot Prodigy machine is stable, consistent, and capable for running the adhesive dispense with targets to achieve the requirement of dot diameter in between 500 to 550 μm, dot weight in between 0.30 mg to 0.33 mg and CpK above 1.33. The results of 27 run DOE optimization process with Taguchi method included the noise of high and low viscosity showed piston distance has the largest effect on the processor yield for both dot weight 0.32 mg and dot diameter 0.5 mm. Parameters range from 200-300 RPM, syringe air from 35-45PSI and piston distance 150 μm. The nominal parameter setting will be RPM is 250, Piston distance is 150 μm and Syringe Air is 40 PSI. A robust production process starts with understanding the adhesives in their fluid state and which important parameters must be optimized, important machine options that must have in the machine for continuing sustain in running production.